THE IMPACT OF ANTI-MÜLLERIAN HORMONE ON INFERTILITY IN MARRIED COUPLES - Adelina Elezi; Sheqibe Beadini; Irena Kostovska; Vegim Zhaku; Albulena Beadini; Albin Beadini; Egzona Ziberi (Faculty of Medical Sciences, Tetova, Republic of North Macedonia, 2025)
Introduction: Anti-Müllerian hormone (AMH) is produced by the granulosa cells of small follicles growing in the ovaries. Serum AMH levels correlate strongly with the number of growing follicles, and therefore AMH has been increasingly recognized as a valuable hormonal marker for the ovaries. Anti-Müllerian hormone (AMH) is a member of the transforming growth factor beta family that takes its name from its role in male sex differentiation by promoting regression of the Müllerian ducts. AMH is best known as a serum marker of ovarian function and as an estimator of AMH values as a hormone for ovarian reserve for the detection of polycystic ovary syndrome. Aim of the study: The main purpose of this paper is the prevalence of infertility in married couples for primary and secondary infertility. This paper aims to investigate the prevalence of infertility in married couples in women for Anti-Müllerian hormone and in men for sperm quality, sperm count and their pathologies in a spermogram by expressing them in percentage and the prevalence of infertility by taking anamnesis from both women and men in married couples of different age groups. Material and method: In this study, sperm samples from men of infertile couples were analyzed, determining the amount of sperm the number of spermatozoa and their motility in men with primary and secondary infertility. In women, in addition to the general anamnesis, an analysis of the Anti-müllerian hormone was performed by taking the blood (serum) of the patients in the study and the measurements of this hormone were tested with the (ELFA) fluorescent immunoassay method with the aparature Vidas. Results: The results of the research will consist of the prevalence of primary and secondary infertility and the level of Anti-müllerian hormone in married couples. The results of the research will also provide a real picture of the situation of married couples suffering from this syndrome. From the research results, recommendations will be given on improving infertility in married couples as a phenomenon that has recently become very concerning for married couples affected by primary and secondary infertility. Conclusion: Male infertility is expressed by a high incidence of decreased sperm quality and sperm damage manifested by asthenozoospermia and teratozoospermia. The level of Anti-müllerian hormone is lower in women in the study with secondary infertility compared to patients in the control group and patients with primary infertility. This paper will serve the field of Gynecology in particular and the field of medicine in general.
Keywords: infertility; semen analysis; primary and secondary infertility; Anti-Müllerian hormone